Personal Exposure of Traffic Policeman to Particulate Matter in Jakarta: Distribution of Size, Chemical Composition, and Work Time - Ramdhan, Doni Hikmat; Ahmad, Eka Fitriani; Kurniasari, Fitri; Rizky, Zuly Prima; Atmajaya, Hardy; Santoso, Muhayatun (Kesmas, 2019)
Particulate matter (PM) is an air pollutant that has an impact on public health, especially in an urban area. The objective of this study was to analyze the personal concentration of PM2.5 and its composition among police working in the roadside area in Jakarta. PM measurement has done to the policeman that controlled traffic on four near highway locations in Jakarta. Sioutas impactor, Leland Legacy personal pump, and quartz fiber filter were chosen to measure the fine particles. Each PM was measured for 8-hour period. PM concentration was analyzed by the gravimetric method while tracing element and black carbon in PM0.25 by energy dispersive X-ray fluorescence (EDXRF) and EEL Smoke Stain Reflectometer. As a result, near highway PM2.5 concentration in Jakarta during weekdays and weekends measurement are 92.18 ± 10.66 μg/m3, and 78.09 ± 11.61 μg/m3. S, K, Fe, Ca, Zn, and Pb are major elements found in all locations. The black carbon concentration in all location was 17 ± 5.7 μg/m3. A high concentration of fine particles, a traffic-related trace element in PM0.25, and black carbon are showed that traffic-related source is the major contributor to a high level of fine particulate matter at near highway locations in Jakarta. The weekday's concentration of PM2.5 and PM0.25 among Jakarta Policemen was higher than in the weekend concentration. A particle with size of less than 0.25 µm dominated the fine particles concentration. Further researcher is expected to see the difference in the effects of traffic-related particulate matter exposure between traffic policeman and police who work at office.